2012
DOI: 10.1111/apt.12160
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse in patients with Crohn's disease in remission after 1 year of biological therapy

Abstract: SUMMARY BackgroundSome of the most important questions relating to the use of biological therapy in inflammatory bowel diseases concern the duration of maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 18 publications
7
63
0
1
Order By: Relevance
“…9,10,[13][14][15] Few studies reported on the long-term outcome of patients after IFX withdrawal when in clinical remission. A Danish retrospective observational study reported a low rate of remission (12%) ten years after the last IFX infusion.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[13][14][15] Few studies reported on the long-term outcome of patients after IFX withdrawal when in clinical remission. A Danish retrospective observational study reported a low rate of remission (12%) ten years after the last IFX infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Within the fi rst year after stopping, 27 % of the patients in both cohorts relapsed. Other studies reported that the following factors associate with the risk of relapse after infl iximab discontinuation: longer disease duration at the time of fi rst infl iximab infusion (CD patients), previous biological therapy (both CD and UC patients), previous dose intensifi cation (CD patients), and age at the time of diagnosis of less than 25 years (CD patients) (20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…These include three retrospective and six prospective studies (11)(12)(13)(19)(20)(21)(22)(23)(24). All nine studies included rather few patients (14 to 121), all but two included only infl iximab stoppers, and only three studies included UC patients.…”
Section: Relapse Rates In Other Studiesmentioning
confidence: 99%
“…With the exception of the study by Sorrentino et al, 35 in which endoscopic remission was reported (100% remission at 80 weeks), most studies only provided rates of clinical remission/ response after re-treatment; in many cases, the information was restricted to the response rates, with no further details. 42,43,50,51,54,58,59,62 The studies by Molnar et al 43 and Monterubbianesi et al 51 reported the lowest response rates (54.7% and 63.3%, respectively) and the highest infusion reaction rates (6% and 10%, respectively). Excluding these studies, remission was safely achieved in a high proportion of patients in all other studies (ranging from 78.3% to 100%).…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 95%
“…Molnar et al found a similar relapse rate of 45% in a study of withdrawal after 3 induction doses of infliximab. 43 Domenech et al found significantly increased relapse rates after stopping scheduled biologic therapy in patients with perianal disease compared with those with luminal disease only (82% vs 17%) after a mean follow-up period of 8.8 months. 40 This finding is also supported by a study by Molnar et al 44 Of the remaining studies, 2 were in a pediatric population.…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%